Neuwied zur Zeit der Freiheitskriege im Spiegel des Diariums der Brüdergemeine Neuwied von 1813 - Raillard, Rainer (2018)
In the Wars of Liberation (1813-1815) the European peoples, above all Russia, Prussia and Austria, rose up against Napoleon's hegemony over Europe. How the Moravian congregation in Neuwied experienced this period is described in the Congregational Diary for 1813. Of especial note are the months of November and December 1813, which saw dramatic events. Neuwied lies directly on the right bank of the Rhine; since 1794 the left bank had belonged to Napoleonic France. Town and congregation were not touched by warfare, however. The billeting of Russian soldiers and officers brought with it -- alongside the restrictions on daily congregational life repeatedly mentioned in the Diary, such as the cancellation of preaching services -- above all material and organizational effort to accommodate and feed the soldiers allocated to the settlement. The stresses and fears that arose because of cultural differences and language barriers between the Russian soldiers and the members of the congregation should not be underestimated. These difficulties were mitigated by the fact that one of the brethren, who had learned Russian while living in Sarepta (today part of Volgograd), was able to serve as an intermediary. Here the Moravian Church's international nature proved a decided advantage. Moreover, the congregation profited from the fact that the Moravian Church was well known. Many Russian commanders and officers were familiar with the church and its institutions. They attended some of the services and were shown round the choir houses. Subjectively at least, the interest shown in the congregation was probably experienced as alleviating the pressure, even though the Diary contains no indications of preferential treatment with regard to the billeting of soldiers. All in all, Neuwied came through the events of the Wars of Liberation relatively unscathed.
Reproduktion
Keywords: 19th century church history; Moravian Church; Napoleonic Wars, 1800-1815; Neuwied (Germany); Wars of Liberation, 1813-1814